Análise do tráfego de spam coletado ao redor do mundo - Pedro Henrique Bragioni Las-casas (2013)
Several efforts have been pursued to create a comprehensive view of spam traffic. However, observations at isolated points of the Internet are always limited by factors of spatial locality. This dissertation aims to add a dimension to this analysis by contrasting samples of spam traffic collected simultaneously at different points. Furthermore, this study aims to evaluate the time factor in the spam traffic, and the impacts caused byit. Our analyses indicate that factors such as location and connectivity have significant impact on the observed traffic, but certain features, such as profiles of messages sent by different protocols, source addresses and test patterns from spammers repeat themselves around the world. We also identified that the spam traffic varies considerably over time, with different patterns in different times.